Relato de caso: piometra com desenvolvimento de ascite e septicemia em coelha doméstica (Oryctolagus cuniculus) - Freitas, Itainara Taili da Silva (Universidade Federal Rural do Semi-Árido, 2018)
In the last decades, rabbits have ceased to be a source of meat, fur and wool to take place in families as pets, since it has been seeking more and more animals that can be created in apartments, that is, that be small, quiet, but show affection to the owner. Along with the intensive coexistence and greater care with these animals, providing them with a greater longevity, they also come with various pathologies, associated both the species and the management adopted, among other individual factors. Thus it is occurring with domestic rabbits in reproductive age and that are not directed to this end: the incidence of reproductive problems such as pyometra, which in this species is associated with hormonal factors and colonization by autochtonous bacteria by ascending route. The challenge for definitive diagnosis of pyometra and its complications in rabbits is in the peculiarities of this species, which requires specialists in the area. In this way, the adoption of ovariohysterectomy in the routine of the surgical clinic of exotic animals has been established in the same way that occurs for small animals, as a preventive form against the disorders of the reproductive tract of these animals.
Monografia
Keywords: Oryctolagus cuniculus; Animais exóticos; Piometra; Ovariohisterectomia; Oryctolagus cuniculus; Exotic animals; Pyometra; Ovariohysterectomy; CIENCIAS AGRARIAS::MEDICINA VETERINARIA